Combined effects of inflorescence developmental age and environmental conditions during microgametogenesis on pollen viability, germination and size in Musa acuminata ssp - Severyns, A.; Swennen, R.; Janssens, S.B.; De Storme, N. (2025)
Background and Aims Male fertility is often suboptimal in parthenocarpic banana cultivars, hindering their use as male parents in current banana breeding schemes. Next to genotype-specific traits such as ploidy and structural heterozygosity, inflorescence developmental age and environmental factors can significantly influence male reproductive performance. Methods In this study pollen viability, germination capacity, and diameter, were closely monitored throughout the entire male flowering phase of Musa acuminata wild diploids, and diploid and triploid cultivars. Additionally, environmental parameters, including temperature, light radiation, and humidity, were monitored up to 40 days before anthesis to determine their influence on microgametogenesis. Results Wild accessions showed a gradual reduction in pollen germination over the flowering period. High light radiation prior to pollen mitosis I and II reduced germination capacity, while during meiosis it negatively affected pollen viability. Conversely, in cultivated bananas, pollen traits improved with the developmental age of the male inflorescence. In these cultivars, higher temperatures during meiosis enhanced pollen diameter, viability, and germination rates. Conclusions These findings indicate that both inflorescence maturity and specific environmental conditions during pollen development significantly influence pollen quality in bananas. Pollen performance could be optimized in wild diploids by obtaining pollen in the first months of the male flowering phase and shielding the plants from high light intensities, whereas for cultivars pollen should be harvested towards the end of the male flowering phase and a heat treatment during meiosis could lead to higher pollen quality and thereby increase breeding success.